Riesgos percibidos de compras por internet en mercados emergentes - Méndez Lazarte, Christiam Ismael (2016)
This research proposes a conceptual model intention of buying a well through an online store, with reference to the perceived risks, web design, trust, incentives, status and profile of customers. The research aims to focus the effect on the perceived risks thus controls the other variables identified. It was taken as a reference to university students in the city of Lima; apply a questionnaire designed with the Likert scale in order to identify the degree of perception of transactional risks, information delivery, social and psychological in purchase intent footwear. Resulting in a high intent to purchase pass a physical store to online, but they are holding back because perceived risks such as delivery time and ability to return the product, as well as social, where potential buyers are criticized by people around them.